Investigating the mediating role of academic self-sufficiency and basic psychological needs in the relationship of social skills and social intelligence with academic achievement - Fatimeh Sabih Mahdi; Hasan ghalavandi (مدیریت و چشم انداز آموزش)
AbstractThe purpose of the present research was to investigate the mediating role of academic self-sufficiency and basic psychological needs in the relationship between social skills and social intelligence with academic progress in the history course among fifth grade literature students in Babol city. The method of the current research was correlative-descriptive. The statistical population consisted of 2110 students of the fifth grade of literature in Babol city, 327 of which were selected by random cluster sampling, using Morgan's table. Five standard questionnaires of social skills of Gresham and Elliott (1990), social intelligence of Silvera et al., (2001), psychological needs of Guardia et al., 2014) was used to collect the research data; the validity of the questionnaire was confirmed, and the reliability of the tool was confirmed using Cronbach's alpha coefficient in a preliminary study for social skills questionnaire 0.86, social intelligence 0.91, psychological needs 0.88, self-sufficiency 0.83, and academic progress 0.90. Data analysis was done using Pearson's correlation coefficient analysis, multiple regression analysis, and path analysis in SPSS and Lisrel statistical software. The results showed that there is a positive and meaningful relationship between social skills, social intelligence, academic self-sufficiency, and basic psychological needs with the academic progress of students. Also the results showed that the mediating role of academic self-sufficiency and basic psychological needs in the relationship between social skills and social intelligence with students' academic progress is positive and meaningful.Extended abstractIntroductionOne of the significant issues in the field of education is the evaluation of the academic progress of students, which is one of the important indicators of the process of evaluating the educational success of educational centers (Martyushev et al, 2014). Academic progress is used as one of the indicators of progress in the education system, the concept of "doing homework and students' success in passing the courses of a specific academic level", or "students' success in learning course material". Academic decline is the negative aspect of it; one of the problems of the educational system, which manifests itself in various ways such as the failure of students to achieve the goals of their respective educational levels, failure and repetition of educational levels, early school leaving, unemployment and indecision (Khazaei, 2016). Studies show that social skills can have a positive and significant effect on the academic progress of students (Pourqorban Gourabi et al, 2021). The category of social skills has become a familiar title that is mentioned in most educational circles and gatherings. This presence starts with the feeling of the importance of life; since these skills have a first-class relationship with the real life of people, talking about them is actually talking about life. In education, like other institutions and organizations, teaching life skills seems necessary (Gregi, 2022).Various research results show that social intelligence can have a positive and significant impact on students' academic progress (Mohammadi et al, 2019; Saxena 2013). Social intelligence is simply the ability to get along and communicate with others. Man is a social being anyway and this is very necessary for us to live and enjoy it (Yermentaeyeva et al, 2014). Based on this, the main problem of the current research is: what is the mediating role of academic self-sufficiency and basic psychological needs in the relationship between social skills and social intelligence with academic progress in the history course among fifth grade literature students in Babol city?Theoretical FrameworkAcademic progressAcademic progress is general or private acquired information or skills in the subject matter, usually measured by tests or marks or both, set for students by teachers. As can be seen in the definition of academic progress, from the concepts and categories of academic progress can deduced that it includes two concepts of knowledge, and information and skills, which is the reason for the title of subjects presented in the educational system. So, we must pay attention to the above two characteristics to operationalize academic progress and measure it (Khazaei, 2016).Social skillsSocial skills are abilities that cause behaviors reinforced positively or negatively. These skills can produce positive and successful results in human relationships with others and provide more adaptation and suitable and favorable effect on the behavior of other members of society with whom the child lives in society. Socialization is a process during which the norms, skills, motivations, and behaviors of a person are formed, and prepares him to enter the society and provides the basis for success in education (Ghasemi, 2014).Social intelligenceSocial intelligence can be considered as the ability to understand and control one's emotions and feelings in order to help intellectual activities, decision-making, and communication (Feizi, 2017).Academic self-sufficiencySelf-sufficiency is a person's perception of his capacities and abilities regarding performance in various fields of life such as education (Aghaie Motlagh, 2021).Basic psychological needsIn psychology, need is a state of deprivation, deficiency, and lack in an organism, such as a lack of food, water, and oxygen; or in general, a lack of any state that is necessary for the continuation of a living being's life, and is necessary for a person's well-being. All living beings, from the simplest protozoan to the most complex and complete human, have a set of needs; whenever an activity activates our psychological needs, we become interested in it. When an activity satisfies our psychological needs, we feel satisfied. Therefore, we are aware of our own feelings of interest and satisfaction, but the reason for engaging in our environment is that psychological needs activate and satisfy us (Shabani, 2014).Kazemi et al, (2022) showed that academic self-sufficiency can affect the academic progress of students.Salkind (2021) showed that the concept of self-beliefs emerged with social learning theory for the first time.Vasile et al, (2011) showed that in Bandura's (1987) socio-cognitive approach, ego is defined as an epistemic reference that includes cognitive structures to provide mechanisms for understanding, evaluating and regulating behavior. Research methodologyThe method of the current research was correlative-descriptive. The statistical population consisted of 2110 students of the fifth grade of literature in Babol city, 327 of which were selected by random cluster sampling, using Morgan's table. Five standard questionnaires of social skills of Gresham and Elliott (1990), social intelligence of Silvera et al, (2001), psychological needs of Guardia et al, 2014) was used to collect the research data; the validity of the questionnaire was confirmed, and the reliability of the tool was confirmed using Cronbach's alpha coefficient in a preliminary study for social skills questionnaire 0.86, social intelligence 0.91, psychological needs 0.88, self-sufficiency 0.83, and academic progress 0.90.Research findingsData analysis was done using Pearson's correlation coefficient analysis, multiple regression analysis, and path analysis in SPSS and Lisrel statistical software. The results showed that there is a positive and meaningful relationship between social skills, social intelligence, academic self-sufficiency, and basic psychological needs with the academic progress of students. Also the results showed that the mediating role of academic self-sufficiency and basic psychological needs in the relationship between social skills and social intelligence with students' academic progress is positive and meaningful. ConclusionThe present study was conducted with the aim of investigating the mediating role of academic self-sufficiency and basic psychological needs in the relationship of social skills and social intelligence with academic progress in the history course among fifth grade students of literature in Babol city. The findings are consistent with the research results of Ahmadi et al, (2013), Nizami et al, (2019), Dehghani et al, (2019), Zinali, Zinali (2022), Kazemi et al, (2022), Esteban et al, (2022), Janke (2022), and Iranmanesh et al, (2020). Esteban et al, (2022) reported that academic self-efficacy, self-esteem, study satisfaction, and the use of virtual media can have a significant impact as predictors of academic progress.The existence of academic self-sufficiency and the fulfillment of basic psychological needs provide a platform for the social skills and social intelligence of students to provide them with the basis for academic progress. Improve the ability learned or acquired from the courses provided. In this regard, it can be observed that the growth of learning academic materials is realized, and the ability learned or acquired from the courses provided is improved. Academic progress of students is one of the important indicators in the evaluation of education. Undoubtedly, in today's advanced world, one of the signs of a person's success is educational progress, without which the development and progress of any country will not be possible.